Receipt of COVID-19 vaccine in preterm-born children aged 3-7 in China - Wang, Dan; Li, Li; Ma, Xiaofeng; Lin, Yunfeng; Chen, Liping; Arigonggaowa,; Peng, Xianglian; Shi, Jingyun; Yang, Jie; Ju, Rong; Li, Zhankui; Cao, Jingke; et al. (Frontiers in Public Health, 2023)
Objectives: To determine the COVID-19 vaccination rate in preterm-born children aged 3-7 in China and influential factors, identify vaccination-related adverse reactions, and clarify reasons behind parental refusal of vaccination to their children.This cross-sectional study was conducted in parents of preterm-born children aged 3-7 in different regions of China through WeChat.Results: Of 1,924 Chinese preterm-born children aged 3-7 included in this study, 1,552 (80.7%) had been vaccinated against COVID-19, with a higher vaccination rate in eastern China. Children older than four years, kids in kindergartens and primary schools, children living in eastern or western China, and children whose fathers had received at least one dose of a COVID-19 vaccine tended to be vaccinated against COVID-19 after adjusting for other covariates. Conversely, children living in urban areas, children whose annual family income was less than 50,000 CNY or more than 300,000 CNY, premature children who underwent hospital transfers, and children with underlying diseases were less likely to get vaccinated. Adverse reactions occurred in 59/1,552 (3.8%) vaccinated children. Parents of 118/372 (31.7%) children expressed their concerns over adverse reactions to COVID-19 vaccination. Other reasons like the absence of information about the place where they could get vaccination were mentioned as well.Conclusions: COVID-19 vaccination-related adverse reactions rarely occurred and most of them were mild among preterm-born children aged 3-7. Higher vaccination coverage can be achieved as parents are provided with more scientific data about benefits of vaccination, vaccination contraindications and precautions, and more information about vaccination sites.